Four-armed Vishnu - Temples of India Project Team (Jio Institute, 2024)
A four-armed Vishnu is depicted seated in the lalitasana posture. He carries a mace and a chakra in his upper right and left hands, respectively, while the lower right and left hands hold a mala and possibly a citron, respectively.